Dietary selenium intakes and musculoskeletal function in very old adults - Perri, Giorgia (2020)
Funding: This individual research study received no additional funding. However, we would like to thank The MRC-Versus Arthritis Centre for Integrated Research into Musculoskeletal Ageing (CIMA) (https://www. cimauk.org/) for funding the PhD programme of study associated with this research. We would also like to acknowledge the generous donations provided by Cumbria Community Foundation and Beverley Charitable Trust Fund throughout the associated PhD programme of study.